Comparison of fixture-based and manual fiber integration in adhesive joints: Effects on strain signal quality - Hermelingmeier, Lucas; Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)

Toward integrated sensors for optimized optical coherence tomography with undetected photons - Roeder, Franz; Pollmann, René; Quiring, Viktor; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (Physical Review Applied)
The development of practical sensors for optical coherence tomography (OCT) with undetected photons requires miniaturization via integration. To be practical, these sensors must exhibit a large spectral bandwidth and a high brightness, which are linked to a high axial resolution and a sufficient signal-to-noise ratio, respectively. Here, we combine these requirements in a scheme for OCT measurements with undetected photons based on nonlinear <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mi>Ti</a:mi> <a:mo>:</a:mo> <a:msub> <a:mrow> <a:mi>Li</a:mi> <a:mi>Nb</a:mi> <a:mi mathvariant="normal">O</a:mi> </a:mrow> <a:mn>3</a:mn> </a:msub> </a:math> waveguides. We investigate the performance benchmarks of the commonly used SU(1,1) scheme in comparison to an induced-coherence scheme and find that the latter is actually better suited when implementing measurements with undetected photons in integrated systems. In both schemes, we perform pump-gain optimization and OCT measurements with undetected photons with an axial resolution as low as <d:math xmlns:d="http://www.w3.org/1998/Math/MathML" display="inline"> <d:mn>28</d:mn> <d:mspace width="0.2em"/> <d:mtext fontfamily="times">μ</d:mtext> <d:mrow> <d:mi mathvariant="normal">m</d:mi> </d:mrow> </d:math> .

Quantum-limited detection of the arrival time and the carrier frequency of time-dependent signals - Folge, Patrick Fabian; Serino, Laura Maria; Mišta, Ladislav; Brecht, Benjamin; Silberhorn, Christine; Řeháček, Jaroslav; Hradil, Zdeněk (Optica)
Precise measurements of both the arrival time and carrier frequency of light pulses are essential for time–frequency-encoded quantum technologies. Quantum mechanics, however, imposes fundamental limits on the simultaneous determination of these quantities. In this work, we derive and experimentally verify the quantum uncertainty bounds governing joint time–frequency measurements. We show that when detection is restricted to finite time windows, the problem is naturally described by a quantum rotor, rendering the commonly used Heisenberg uncertainty relation inapplicable. We further propose an optimal detection scheme that saturates these fundamental limits. By sampling the Q -function, we demonstrate the reconstruction of the Wigner function beyond the harmonic oscillator. Using an experimental implementation based on a quantum pulse gate, we confirm that the proposed scheme approaches the ultimate quantum limit for simultaneous time–frequency measurements. These results provide a framework for joint time–frequency detection with direct implications for precision measurements and quantum information processing.

Molecular lithography with DNA nanostructures: Methods and applications - Keller, Adrian Clemens; Linko, Veikko (Journal of Physics D: Applied Physics)
Abstract Lithographic surface patterning is a cornerstone of modern materials and device fabrication. Although the available lithography techniques are constantly being advanced to push the feature sizes down to the few-nanometer scale, such developments are associated with many technological and economic challenges. Combining established top-down lithography with bottom-up self-assembly strategies has the potential to overcome those challenges and enable the manipulation of matter with molecular precision. One of the most exciting approaches in this regard is to harness the programmability of DNA self-assembly to create precise DNA nanostructure masks to be used in the lithographic patterning of diverse substrates. DNA nanotechnology has provided us with a versatile toolbox for the high-yield synthesis of 2D and 3D nanostructures with complex, user-defined shapes at unprecedented molecular accuracy. Consequently, the last decade has seen intense research efforts aimed at transferring such DNA nanostructure shapes into functional organic and inorganic materials and we have now arrived at a point where sophisticated molecular lithography approaches utilize DNA nanostructure masks for the fabrication of plasmonic surfaces for metamaterials and sensing applications. This review summarizes how the spatial information of such DNA nanostructure masks can be transferred into various organic and inorganic materials through selective etching and deposition steps. The review also discusses recent developments toward all-purpose molecular lithography schemes and highlights promising extensions of the discussed methods toward new materials systems and application fields.

Cayley Commutator-free Methods for Krotov-Type Algorithms in Quantum Optimal Control - Wembe, Boris; Ali, Usman; Meier, Torsten; Ober-Blöbaum, Sina
This paper presents a class of structure-preserving numerical methods for quantum optimal control problems, based on commutator-free Cayley integrators. Starting from the Krotov framework, we reformulate the forward and backward propagation steps using Cayley-type schemes that preserve unitarity and symmetry at the discrete level. This approach eliminates the need for matrix exponentials and commutators, leading to significant computational savings while maintaining higher-order accuracy. We first recall the standard linear setting and then extend the formulation to nonlinear Schrödinger and Gross-Pitaevskii equations using a Cayley-polynomial interpolation strategy. Numerical experiments on state-transfer problems illustrate that the CF-Cayley method achieves the same accuracy as high-order exponential or Cayley-Magnus schemes at substantially lower cost, especially for longtime or highly oscillatory dynamics. In the nonlinear regime, the structure-preserving properties of the method ensure stability and norm conservation, making it a robust tool for large-scale quantum control simulations. The proposed framework thus bridges geometric integration and optimal control, offering an efficient and reliable alternative to existing exponential-based propagators.

Practical considerations for assignment of photon numbers with SNSPDs - Schapeler, Timon; Mischke, Isabell; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) can enable photon-number resolution (PNR) based on accurate measurements of the detector’s response time to few-photon optical pulses. In this work, we investigate the impact of the optical pulse shape and duration on the accuracy of this method. We find that Gaussian temporal pulse shapes yield cleaner arrival-time histograms and, thus, more accurate PNR, compared to bandpass-filtered pulses of equal bandwidth. For low system jitter and an optical pulse duration comparable to the other jitter contributions, photon numbers can be discriminated in our system with a commercial SNSPD. At 60 ps optical pulse duration, photon-number discrimination is significantly reduced. Furthermore, we highlight the importance of using the correct arrival-time histogram model when analyzing photon-number assignment. Using exponentially modified Gaussian distributions, instead of the commonly used Gaussian distributions, we can more accurately determine photon-number misidentification probabilities. Finally, we reconstruct the positive operator-valued measures of the detector, revealing sharp features that indicate the intrinsic PNR capabilities.

Experimental entropic uncertainty relations in dimensions three to five - Serino, Laura Maria; Chesi, Giovanni; Brecht, Benjamin; Maccone, Lorenzo; Macchiavello, Chiara; Silberhorn, Christine (Physical Review A)
We provide experimental validation of tight entropic uncertainty relations for the Shannon entropies of observables with mutually unbiased eigenstates in high dimensions. In particular, we address the cases of dimensions <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi>d</a:mi> <a:mo>=</a:mo> <a:mn>3</a:mn> </a:mrow> </a:math> , 4, and 5 and consider from 2 to <b:math xmlns:b="http://www.w3.org/1998/Math/MathML"> <b:mrow> <b:mi>d</b:mi> <b:mo>+</b:mo> <b:mn>1</b:mn> </b:mrow> </b:math> mutually unbiased bases. The experiment is based on pulsed frequency bins measured with a multioutput quantum pulse gate, which can perform projective measurements on a complete high-dimensional basis in the time-frequency domain. Our results fit the theoretical predictions: the bound on the sum of the entropies is never violated and is saturated by the states that minimize the uncertainty relations.

Brownian Motion With Partial Resetting Conditioned to Stay Positive - Kolb, Martin; Wübker, Achim (Bulletin of the London Mathematical Society)
Abstract We consider Brownian motion with partial resetting, which has recently attracted a lot of attention in physics as well as the mathematics literature. We analyze the speed of convergence of this process towards stationarity as well as its quasistationary behavior. In particular, we prove the existence of a Yaglom limit and hence of a minimal quasistationary distribution. We use these results to study our main topic, namely the process conditioned on staying positive using methods which are well adapted to this specific process. It turns out that this process can be described explicitly as a three‐dimensional Bessel process with partial resetting with the same parameter but a modified resetting rate. This can be interpreted as an effect due to entropic repulsion.

Defect Structure-Performance Correlation in Eu³⁺@UiO-66: Design of Coordination Sites for Rapid Optical O₂ Sensing - Zhao, Zhenyu; Tiemann, Michael (Journal of Materials Chemistry C)
Defect engineering offers an effective route to tailor the local coordination environment, gas transport and excited-state processes in metal-organic frameworks (MOFs). We establish a quantitative structure-property relationship linking defect-modulated porosity...

Data Spaces for Heterogeneous Data Ecosystems – Findings from a Design Study in the Cultural Sector - zur Heiden, Philipp; Halimeh, Haya; Hansmeier, Philipp; Vorbohle, Christian; Althaus, Maike; Beverungen, Daniel; Kundisch, Dennis; Müller, Oliver (Communications of the Association for Information Systems)

Selective Use of Yannakakis’ Algorithm for Consistent Performance Gains - Böhm, Daniela; Gottlob, Georg; Lanzinger, Matthias; Longo, Davide Mario; Okulmus, Cem; Pichler, Reinhard; Selzer, Alexander (Proceedings of the 28th International Workshop on Design, Optimization, Languages and Analytical Processing of Big Data (DOLAP 2026))
Large intermediate results can cause join queries to run unexpectedly long. This problem is particularly common for analytical queries, which aggregate data over many tables to produce a comparatively small final output, and queries on graph data, where intermediate results blow up quickly. Recent work inspired by Yannakakis’ algorithm approaches this by modifying the query engine to avoid materializing unnecessary tuples. However, this requires significant changes to the core of the system, which is not feasible in many situations such as cloud environments or proprietary systems. In this work, we propose a flexible approach for optimizing long-running join queries from the outside of the DBMS. Rewriting-based realizations of Yannakakis’ algorithm suffer from inherent overhead due to the creation of intermediate tables. Thus, we present an approach for detecting and targeting queries which would benefit from a Yannakakis-style optimization. We introduce a new benchmark combining 5 standard benchmarks and augmenting them with additional instances, which provides a sufficient size and diversity for a machine learning based solution. On PostgreSQL, DuckDB and SparkSQL, slowdowns on queries where the rewriting is counterproductive are mostly avoided, as opposed to a naïve application of the rewriting, and we observe significant improvements in end-to-end runtimes over standard query execution and unconditional rewriting.
Keywords: Join Queries; Acyclic Queries; Query Processing

Reason and Communication: Jürgen Habermas’s Legacy for Media and Communication Studies - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Bridging the Dual Nature: How Integrated Explanations Enhance Understanding of Technical Artifacts - Terfloth, Lutz; Buhl, Heike M.; Lohmer, Vivien; Schaffer, Michael; Kern, Frederike; Schulte, Carsten

Retrospective video recall for analyzing cognitive processes in naturalistic explanations - Lazarov, Stefan Teodorov; Schaffer, Michael; Gladow, Viviane; Buschmeier, Hendrik; Buhl, Heike M.; Grimminger, Angela
In this paper, we discuss the application of retrospective video recall for the assessment of cognitive processes in explanatory interactions, such as understanding and mental models. Our purpose is to reflect on the benefits and limitations of video recall compared to another self-report method, ‘thinking-aloud’. To do so, we reveal empirical results from the application of video recall in three interdisciplinary research projects that applied the method for the qualitative and quantitative assessment of cognitive and behavioral phenomena in everyday explanations. In all three projects, video recall was applied as a post-hoc procedure following the recording of dyadic face-to-face explanations of board games. The design of the video recall procedure differed between individual projects because they pursued different research objectives – that is the investigation of (1) an interlocutor's multimodal signals of understanding, (2) the change in assumptions about an interlocutor's dispositional and situational knowledge, and (3) the differentiated assessment of an interlocutor's developing understanding of domain knowledge aspects by distinguishing between mechanistic and functional explanatory stances. By discussing the benefits and the limitations of each procedure, this article provides critical reflections on video recall as a versatile research method applied for the analysis of human multimodal behavior in interaction and cognitive processing.

Aggregation Processes in Customer Rating Systems - Insights from an Economic Decision Experiment - van Straaten, Dirk; Mir Djawadi, Behnud; Melnikov, Vitalik; Hüllermeier, Eyke; Fahr, René (SSRN Electronic Journal)
The aggregation of rating metrics in reputation systems is crucial for mitigating information overload by condensing customer rating distributions into singular valence scores. While platforms typically employ technical aggregation functions, such as the arithmetic mean to capture product quality, it remains unclear whether these functions align with customers' innate aggregation patterns. To address this knowledge gap, we designed a controlled economic decision experiment to elicit customers' aggregation principles by analyzing their product ranking decisions and contrasting these with various reference functions. Our findings indicate that, on average, customers aggregate rating information in accordance with the arithmetic mean. However, a granular analysis at the individual level reveals significant heterogeneity in aggregation behavior, with a substantial cluster exhibiting binary patterns that focus equally on negative (1-2 star) and positive (4-5 star) ratings. Additional clusters concentrate on negative feedback, particularly 1-star ratings or 1-2 star ratings collectively. Notably, these inherent aggregation patterns exhibit stability across variations in numerical information presentation and are not significantly influenced by individual characteristics, such as online shopping experience, risk attitudes, or demographics. These findings suggest that while the arithmetic mean captures average consumer behavior, platforms could benefit from offering customizable aggregation options to better cater to diverse user preferences for processing rating distributions. By doing so, platforms can enhance the effectiveness of their reputation systems and improve the overall quality of decision-making for consumers.

Migration and Long-Term Demographic Change: Can We Control the Numbers? - Abbink, Klaus; Mir Djawadi, Behnud (SSRN Electronic Journal)
In many Western societies, mass immigration has been one of the most divisive policy issues in recent years. Seemingly moderate inflows of migrants can have substantial demographic consequences in the long run, due to (1) higher fertility of the migrant population, (2) its younger age distribution, and (3) the possibility of family reunification. Yet, demography hardly appears in the policy debate, even in media outlets that are critical of mass immigration. This may indicate that the mechanics of population dynamics are not widely understood. We design a laboratory experiment in which we confront subjects with 30 different migration scenarios. Subjects have to decide when to stop a given inflow of migrants to achieve a target share of migrants after 60 years. In line with all our pre-registered hypotheses, in scenarios that contain elements of usual mass immigration the growth of the migrant population is systematically underestimated. This bias is even stronger in scenarios that closely resemble the German situation since the opening of the borders during the 2015 refugee crisis.

Dishonesty of Parents and Children – Evidence from a Field Experiment - Mir Djawadi, Behnud (SSRN Electronic Journal)

Decentring the governance of AI in the military: a focus on the postcolonial subject - Bhila, Ishmael (AI and Ethics)
The governance of emerging technologies with increased autonomy in the military has become a topical issue in recent years, especially considering the rapid advances in artificial intelligence and related innovations in computer science. Despite this hype, the postcolonial subject’s position has been seen as secondary, often associated with victimhood or obscurity. By shifting the narrative to highlight the postcolonial subject’s agency—not only in providing real-world examples of artificial intelligence use in the military but also in knowledge creation and shaping the discourse on governance within the international, this paper contributes to an area of research that is often overlooked. The paper unpacks the norm-making efforts of postcolonial subjects regarding emerging military technologies. In doing this, the paper aims to advance postcolonial theory by showing how the dynamics of governing emerging military technologies intertwine with postcolonial subjectivity and to broaden the academic discussion on the governance of emerging military technologies and algorithmic violence, which has so far been dominated by Western or universalistic discourse.

Praxisschock oder Kohärenz? – Retrospektive Einschätzungen von Berufseinsteiger*innen zu den Phasen der Lehrkräftebildung - Homt, Martina

Behind the Mask: Investigating the Influence of Pseudonymity on Polarization Dynamics in Social Virtual Reality - Tölle, Laura; Rose, Robert; Trier, Matthias